Battery‐integrated multi‐input step‐up converter for sustainable hybrid energy supply. Issue 4 (1st April 2019) - Seyed Mahmoodieh, Mir Esmaeel; Deihimi, Ali
Abstract : This paper presents a battery‐integrated multi‐input step‐up DC–DC converter (BI‐MISUC) as a unified interface for multiple energy sources in the frame of a sustainable hybrid energy supply. The proposed converter comprises one bidirectional port for a battery and several unidirectional input power ports. Battery can be charged by input sources, discharged into load or bypassed while charging/discharging durations are independent of switching duty ratios for input sources. In the presented BI‐MISUC, higher voltage gains with lower duty ratios are achieved not only by increasing the number of inputs but also using the switched inductor (SI) modules. It therefore enables BI‐MISUC to be used for a wide range of applications from low to high voltage/power. Furthermore, input sources can be operated individually or simultaneously to supply load energy at the desired output voltage. The converter operation is described for three scenarios (i.e. no battery, battery charging and discharging). A linear quadratic regulator (LQR) control is also used to regulate the output voltage and output power of input sources at the desired references for different scenarios. Finally, the performance of the BI‐MISUC is validated by simulations and experimental results.